Is Sin Always a Sin? The Interaction Effect of Social Norms and Financial Incentives on Market - LIU, Yanju (Institutional Knowledge at Singapore Management University, 2011)
Using alcohol, tobacco, and gaming consumption data and people’s attitudes toward these sin products to proxy for the social norm acceptance level, we examine how social norms and financial incentives jointly affect the decisions of investment professionals and managers of these “sin” companies. We find that institutional investors’ shareholdings and analyst coverage of “sin” companies are increasing in the degree of social norm acceptance and that the association between shareholdings/coverage and social norm acceptance is less pronounced for firms with higher future expected performance. We also show that managers’ opportunistic behavior, proxied by discretionary accruals and analyst meet-or-beat frequencies, is negatively related to the extent of social norm acceptance and that the association between the degree of opportunism and social norm acceptance is less pronounced for firms with higher financial performance. Our results suggest that social norms and financial incentives have a powerful interaction effect in determining the behavior of market participants, suggesting that social norms can be crossed when motive and opportunity exist.